The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.0902-0055.2004.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of cranberry juice on attachment of oral streptococci and biofilm formation

Abstract: Cranberry juice is known to inhibit bacterial adhesion. We examined the inhibitory effect of cranberry juice on the adhesion of oral streptococci strains labeled with [3H]-thymidine to saliva-coated hydroxyapatite beads (s-HA). When the bacterial cells were momentarily exposed to cranberry juice, their adherence to s-HA decreased significantly compared with the control (P < 0.01). Their hydrophobicity also decreased dependently with the concentration of cranberry juice. We also evaluated the inhibitory effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
110
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(114 citation statements)
references
References 36 publications
2
110
0
2
Order By: Relevance
“…This suggests that susceptibility of mutans streptococci to cranberry polyphenol differs among strains. In an earlier study, cranberry juice showed no influence on growth of S. mutans MT8148R 15) . The cranberry polyphenol fraction used in this study may have contained higher doses of active components than that of cranberry juice.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This suggests that susceptibility of mutans streptococci to cranberry polyphenol differs among strains. In an earlier study, cranberry juice showed no influence on growth of S. mutans MT8148R 15) . The cranberry polyphenol fraction used in this study may have contained higher doses of active components than that of cranberry juice.…”
Section: Discussionmentioning
confidence: 79%
“…Biofilm is a mass of bacteria capable of evading host defense mechanisms and resisting antibiotics. We demonstrated that polyphenol fraction inhibited biofilm formation, and in former studies, we reported that high molecular mass constituents of cranberry juice such as nondialyzable material (NDM) inhibited the biofilm formation of oral streptococci 15) . Poly 100, 500 mean cranberry polyphenol, 100 or 500g/ml, respectively.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is possible that the same process is occurring in our adhesion assays. Other foods and beverages which are capable of inhibiting adhesion of cariogenic bacteria to S-HA include herbal extracts, cranberry juice and water-soluble protein fraction (WSPF) from hen-egg yolk, where 80, 90 and 61% inhibition of S. mutans adhesion to HA has been reported using 5, 250 g L -1 and 5 mg mL -1 of test substance, respectively [7,27,28].…”
Section: Assessment Of Anti-adhesive Effect Of Milk Componentsmentioning
confidence: 99%
“…These biological activities have mainly been attributed to the polyphenol fraction. Polyphenols are naturally present in a number of foods and drinks, such as tea (12), coffee (5), wine and grape juice (3,33), beer and hops (32), cranberry juice (11,34,36,37), cocoa (23), apple juice (38), and many others (28). In a previous study, we have also shown that people who regularly consume foods and drinks containing polyphenols have lower levels of culturable bacteria in their saliva and dental plaque (27).…”
mentioning
confidence: 99%